ANALISIS MISKONSEPSI PESERTA DIDIK MENGGUNAKAN TES DIAGNOSTIK FIVE-TIER MATERI SUHU DAN KALOR DI SMP NEGERI 17 PONTIANAK - Sulastri, Sulastri (Jurnal Inovasi Penelitian dan Pembelajaran Fisika, 2024)
This research is a descriptive study with a survey method that aims to describe students' misconceptions using a five-tier diagnostic test at SMP NEGERI 17 Pontianak on the material of Temperature and Heat. The sample in this study was 150 students. Data collection was carried out through a written test consisting of 8 questions with five levels (five-tier). Based on the results of the validation of the questions by experts, it was obtained that the validity value of the questions was 0.79, which means that the questions were in the high validity qualification. Students' misconceptions using the five-tier diagnostic test obtained average results per indicator, on the indicator of understanding the concept of temperature and measuring instruments, the percentage of students' misconceptions was 41%, then the indicator of understanding the concept of heat and heat transfer, the percentage of students' misconceptions was 34%, the indicator explaining the effect of heat on changes in state, the percentage of students was 37% and the indicator analyzing the effect of temperature changes on the size of objects (expansion) the percentage of students' misconceptions was 40%. From the average per indicator of misconceptions, a percentage result of 38% can be obtained. The results of the study showed that students' misconceptions using the five-tier diagnostic test were categorized as moderate. Therefore, it is expected that teachers can improve students' misconceptions using the five-tier diagnostic test and students can be trained well, especially on students' misconceptions using the five-tier diagnostic test in order to improve students' conceptual understanding.